2006
DOI: 10.1177/0265407506060181
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive responses to betrayal: Type of relationship, victim’s sex, and nature of aggression

Abstract: The present investigation explored young adults’ aggressive responses to hypothetical and actual episodes of betrayal. In two studies, we tested the following hypotheses: (a) aggressive responses would be most severe in romantic relationships when compared with friendships; (b) men and women would respond similarly to betrayal; and (c) verbal aggression would be more frequently described than physical and psychological aggressive tactics. Participants endorsed greater use of verbal aggressive tactics in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
2
23
0
2
Order By: Relevance
“…When trust is betrayed, it hurts. Betrayal elicits a range of negative emotions (Fehr & Baldwin, 1996;Jones & Burdette, 1994) and may even evoke a variety of aggressive behavior (Haden & Hojjat, 2006). Betrayal reflects an erroneous decision to trust and it often leads to a reassessment of the relationship (Finkel et al, 2002;Lewicki & Bunker, 1996).…”
Section: The Violation Of Trustmentioning
confidence: 99%
“…When trust is betrayed, it hurts. Betrayal elicits a range of negative emotions (Fehr & Baldwin, 1996;Jones & Burdette, 1994) and may even evoke a variety of aggressive behavior (Haden & Hojjat, 2006). Betrayal reflects an erroneous decision to trust and it often leads to a reassessment of the relationship (Finkel et al, 2002;Lewicki & Bunker, 1996).…”
Section: The Violation Of Trustmentioning
confidence: 99%
“…Whereas men are more likely to respond to infidelity with violence (e.g., Daly and Wilson 1988; but see Haden and Hojjat 2006), women are more likely to respond by distancing themselves from the relationship (Jankowiak et al 2002). In addition, when Shackelford et al (2002) asked participants to imagine scenarios in which they had been cheated on and to consider their potential responses, they found that men were more likely than women to endorse terminating a relationship following a partner's sexual infidelity.…”
Section: Sex Differences In Correlates Of Infidelitymentioning
confidence: 99%
“…Motivos y reacciones ante la infidelidad en población universitaria el impulso mientras que las mujeres lo suelen hacer más debido a la insatisfacción con su pareja (Brand y cols., 2007;Haden y Hojjat, 2006;Shackelford y Goetz, 2008;Tidwell y Eastwick, 2013).…”
Section: íNdex 217unclassified